Redução de arrasto por adição de goma diutana em escoamentos turbulentos - Santos, Walber Ronconi dos (2019)
The drag reduction phenomenon by addition of small amounts of polymer has been known for more than 70 years. The synthetic polymers Polyethylene Oxide (PEO) and Polyacrylamide (PAM) and the biological polymer Xanthan Gum (XG) are some of the most used drag reducing agents. Research on a recent biopolymer, called Diutan Gum(DG), shows promising results concerningits drag reduction ability. However, its rheological characteristics and advantages compared toother polymers lack further information. With this objective, the diutangum is analyzed in terms of viscosity, storage and loss moduli, and its effects as adragreducing agent. It is verified that the diutangum presents high pseudoplastic behavior, even for concentrations as low as 25 ppm. The elastic modulus is more prominent than the viscous modulusfor a wide frequency range and concentrations above 750 ppm. In the experiments, the reduction of drag provided by diutangum is compared with that of PEO, PAM and XG. In addition, the results are shown in terms of pressure drop and relative drag reduction. It is noted that diutan gumis poorly de-aggregatedand leads toa superior drag reduction compared to other polymers. Diutan gum, like any biopolymer, experiencesbiological degradation, but it can preserve good results up to 10 days afterthepreparation of the solution. The effect of the DG andPEOblendingis also investigated. In addition to the results indicatingpositive synergy fromthe rigid polymer with flexible, the blend attenuated the effects of the degradation suffered by the synthetic.